Narrativizing Memory’s End: A Critical Overview of Contemporary Indian English Dementia Narratives - Chowdhury, Mousana Nightingale; Jain, Payal (SARE: Southeast Asian Review of English, 2025)
This paper provides an overview of contemporary Indian English narratives of dementia, exploring the complex interplay between narrative strategies and the representation of dementia subjectivity, reflecting wider socio-cultural attitudes toward the illness. The study examines Indian fiction and non-fiction published in English since the 21st century in the wake of a firm disability consciousness globally. By analysing six concurrent caregiver memoirs and fictional texts produced in the Indian literary scene, namely, In the Line of Alzheimer’s: The Mission Continues (2009) by S. P. Bhattacharjya, Krishna: Living with Alzheimer’s (2015) by Ranabir Samaddar, A World Within (2014) by Minakshi Chaudhry, Our Nana was a Nutcase (2015) by Ranjit Lal, Girl in White Cotton (2020) by Avni Doshi, and Mrs. C Remembers (2017) by Himanjali Sankar, the research underscores the challenges in representing the lived experiences of dementia vis-à-vis issues of identity, memory, and aging. The paper explores the ethical dilemmas in narrating dementia – balancing agency, limitations of empathy, and politics of representation, alongside the convergence of biomedical and socio-cultural discourses that influence how dementia is portrayed, understood and treated. The study concludes with insights into contemporary dementia narratives and suggests future interdisciplinary research directions within the Indian context.